Investigating the strategic influence of customer satisfaction on firm financial performance - Dotson, Jeffrey (Henry Stewart Talks, 2010)
Formal definition of strategic and tactical marketing decisions, Linking customer and employee satisfaction to firm performance, Models of simultaneous supply and demand, Approaches to optimal allocation of marketing resources